Hidrogelne obloge za vlažno celjenje ran s proteinsko učinkovino - Rošic, Romana (Farmacevtski vestnik, 2010)
Modern approach in the wound healing is based on maintenance of moist environment on the wound and as modern dressings hydrogels have been offered. Based on diffrent researches the healing of the wound can be improved by application of growth factors or proteasećs inhibitors. In the article the development of hydrogels from hydroxyethylcellulose or xantan in different concentrations and with incorporated model protein is presented. Hydrogels from 3% hydroxyethycellulose or 6% xantan posess appropriate rheological characteristics, regardless to the medium used (water, phosphate buffer), sterilization process or way of freezing before lyophilization. The mild technologic conditions of preparation prevent denaturation of the native structure of protein. A new method for release studies was developed, due to the fact that established pharmacopoeial models do not simulate chronic woundćs state. The method enables proteinćs release directly into the medium without barrier through longer period of time. The release of protein from hydroxyethylcellulose hydrogel is controlled by diffusion and in 4 days around90% of incorporated protein has been released. Hence, such hydrogel enables moist wound environment and incorporation of proteasećs inhibitor, which might help to regain the balance between growth factors and proteases inthe wound, what could decrease inflammation and guarantee faster healing.
Keywords: farmacevtski preparati; hidrogeli; rane